Cumulative risk and protection effect of serotonergic genes on male antisocial behaviour: results from a prospective cohort assessed in adolescence and early adulthood. (26th November 2018) - Langevin, Stephanie; Mascheretti, Sara; Côté, Sylvana M.; Vitaro, Frank; Boivin, Michel; Turecki, Gustavo; Tremblay, Richard E.; Ouellet-Morin, Isabelle
Abstract : Background: Heritability of antisocial behaviour is estimated at approximately 50% and involves multiple genes. Aims: To investigate the cumulative genetic effects of 116 single nucleotide polymorphisms mapping to 11 candidate serotonergic genes and antisocial behaviours, in adolescence and in early adulthood. Method: Participants were 410 male members of the Quebec Longitudinal Study of Kindergarten Children, a population-based cohort followed up prospectively from age 6 to age 23. The serotonergic genes were selected based on known physiological processes and prior associations with antisocial behaviours. Antisocial behaviours were self-reported and assessed by using semi-structured interviews in adolescence and in adulthood. Results: Cumulative, haplotype-based contributions of serotonergic genes conferring risk and protection for antisocial behaviours were detected by using multilocus genetic profile risk scores (MGPRSs) and multilocus genetic profile protection scores (MGPPSs). Cumulatively, haplotype-based MGPRSs and MGPPSs contributed to 9.6, 8.5 and 15.2% of the variance in general delinquency in adolescence, property/violent crimes in early adulthood and physical partner violence in early adulthood, respectively. Conclusions: This study extends previous research by showing a cumulative effect of multiple haplotypes conferring risk and protection to antisocial behaviours in adolescence and early adulthood. The findings further support the relevance of concomitantly considering multiple serotonergic polymorphisms to better understand the genetic aetiology of antisocial behaviours. Future studies should investigate the interplay between risk and protective haplotype-based multilocus genetic profile scores with the environment. Declaration of interest: I.O.-M. holds a Canada Research Chair in the developmental origins of vulnerability and resilience.